HUBUNGAN PEMAKAIAN KB SUNTIK 3 BULAN DENGAN KENAIKAN BERAT BADAN DI TPMB BIDAN TITIN DURATUL KABUPATEN TANGERANG BANTEN TAHUN 2023 - Sodikoh, Ikoh; Sutarno, Maryati (INVOLUSI: Jurnal Ilmu Kebidanan, 2024)
ABSTRAK Three-month injectable contraception offers benefits but also carries a risk of adverse consequences for users. Three-month injectable contraception has many benefits, such as being extremely effective, preventing long-term pregnancy, having no effect on husband-wife relationships, not containing estrogen, which means it has no significant effect on blood clotting disorders or heart disease, having no effect on breast milk production, having few side effects, and being safe for use by women over the age of 35 until perimenopause. However, menstruation disorders, depression, vaginal discharge, acne, nausea, vomiting, hair loss, changes in libido, and most importantly, a change in body weight are common adverse effects. The typical rise in body weight is within reasonable bounds, ranging from less than 1 kg to 5 kg in the first year, or eleven pounds or five kilograms, and a 3.4% rise in body fat after three years of consumption. The research design uses a correlational approach with a cross - sectional approach. Data processing was carried out univariately and bivariately with the Chi Square (X2) statistical test. Using 41 respondents who used injectable birth control for 3 months. The statistical test (chi square) yielded a p value of 0.01—that is, a p value less than the alpha value of 0.05—so Ho is rejected and Ha is approved. The result was that "there is a significant relationship between the use of 3-month injectable birth control and weight gain." Keywords:3-monthvaccination,bodyweight